Effects of Wrapping Materials on the Microbial Population of Steam Bean Pudding (Moimoi) - JP, Omorodion Nnenna; John, Wisdom (Journal of Food Technology Research, 2022)
The effects of wrapping materials on the microbial population of Moimoi were assessed. A total of thirty samples of wrapped Moimoi of plastic, waterproof and aluminum foil was collected from food vending sites located in Choba. The samples were taken to the laboratory and analyzed using standard microbiological methods. The total prevalence of bacteria that occurred from foil Moimoi were Micrococus (35%), Bacillus (25%) , Staphylococcus (20%) and Proteus (20%). The total prevalence of bacteria obtained on plastic Moimoi were Staphylococcus (27%), Bacillus subtilis (23%) Proteus sp (23%), Micrococcus sp (13%) and Bacillus cereus (14%). Total prevalence obtained from nylon Moimoi were Staphylococcus (27%), Bacillus cereus (23%), Proteus (18%), Micrococcus (18%) and Bacillus subtilis (14%). The mean total bacteria count, Staphylococcus count and coliform count obtained ranged from 9.8 x103 - 1.35 x103 cfu/g. The result of the study further shows that most of the gram-positive isolates such as Staphylococcus sp, Micrococcus sp, Bacillus subtilis and Bacillus cereus were resistant to antibiotics of ceftriaxone, cloxacillin, Augmentin, ceftazidime and cefuroxime while the gram-negative bacteria isolated Proteus sp was resistance to Augmentin and cefuroxime but susceptible to gentamycin, erythromycin and cefuroxime. Contamination of these wrapped Moimoi samples is due to poor personal hygiene and sanitation among food handlers. To prevent outbreak of food poisoning, users of this wrapping materials should wash wrapping materials with clean water before using and food in these wrapping materials should be consumed immediately to reduce multiplication of microorganisms.